Study on toxicity and environmental safety of glyphosate to aquatic organisms - ZHU Guo-nian; LOU Zhen-yun; SUN Jin-he (浙江大学学报. 农业与生命科学版, 2000)
The toxicity and the dosage-response of glyphosate on aquatic organisms are introduced in the paper. The results showed that glyphosate was low toxic to fish (psudorasobora parva, LC50, 24-96h> 403.8 mg/L), daphnia (daphnia pulex, LC50, 24h=20.04 mg/L) and algae (scenedesmus obliquus, EC50, 24-120h>308.6 mg/L), and the daphnia was the most sensitive to glyphosate among the aquatic organisms. The results also showed that the disappearance of glyphosate in water was very fast and it was less than 0.01 mg/L on the sixth day after application, and glyphosate could be absorbed on sediments while disappeared slowly.